2006
DOI: 10.1097/01.mlr.0000196978.34283.a6
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Medicare Claims for Breast Cancer Chemotherapy Compared With Medical Chart Reviews

Abstract: Of cases identified as receiving chemotherapy by Medicare claims, 97% had strong evidence and only 3% had weak evidence for receiving this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 40 publications
4
73
0
Order By: Relevance
“…SEER provided reliable information that was validated by SEER staff, and Medicare data have been both externally and internally validated by many researchers. 33,43,44 However, we cannot exclude the possibility of misclassification of the factors that may have resulted from modeling categorized variables that were originally continuous and measured with nondifferential error. 45 In summary, this study has shown that ADT was not associated with significantly increased survival benefit in older men with locoregional CaP living in the community.…”
Section: Androgen Deprivation Therapy and Prostate Cancer Survival L mentioning
confidence: 99%
“…SEER provided reliable information that was validated by SEER staff, and Medicare data have been both externally and internally validated by many researchers. 33,43,44 However, we cannot exclude the possibility of misclassification of the factors that may have resulted from modeling categorized variables that were originally continuous and measured with nondifferential error. 45 In summary, this study has shown that ADT was not associated with significantly increased survival benefit in older men with locoregional CaP living in the community.…”
Section: Androgen Deprivation Therapy and Prostate Cancer Survival L mentioning
confidence: 99%
“…[31][32][33][34][35][36] In brief, patients with breast cancer were defined as having received chemotherapy if any of the following Medicare procedure codes was present in the physician or outpatient Medicare claims data 37-40 : the International Classification of Diseases (9th revision, clinical modification) procedure code 9925 and V codes of V58.1, V66.2, or V67.2 37 ; the common procedure codes of 96400 to 96549, J8530 to J8999, J9000 to J9999, or Q0083 to Q0085 38,39 ; and revenue center codes of 0331, 0332, or 0335. 40 The dosage and intensity of chemotherapy were not reliably identified through Medicare claims data.…”
Section: Study Variablesmentioning
confidence: 99%
“…A solution to this problem is to supplement clinical trial results with observational results. Prior research has shown Centers for Medicare and Medicaid Services (CMS) data accurately measure chemotherapy use [5][6][7][8] and the important end point of disease-free survival, 9 but the extent to which CMS data accurately measure the toxicity outcomes traditionally reported in clinical trials is not yet known.…”
Section: Introductionmentioning
confidence: 99%